Bimbingan Pasca Rehab oleh Pembimbing Kemasyarakatan Terhadap Klien Anak Kasus Narkotika dengan Metode BPSS (Biologik, Psikologi, Spritual, dan Sosial) - Sariadi, Banias; Herman, Asep (UNES Law Review, 2023)
Children are the asset and future of the struggle of nations to realize their ideals. As part of the younger generation, children have a very important role and have special characteristics. However, in everyday life, children are often found involved in legal issues or cases, especially drug criminal law. Behavioral deviations, such as drug addicts, are basically victims of drug abuse. Method: In accordance with Article 11 of the 2012 Law on the Protection of Children from Domestic Violence (UU SPPA), a child subject to domestic violence is defined as an infant who is considered to be in conflict with the law, a child who becomes a victim of domestic violence, and a child who becomes a victim of domestic violence. Findings: In accordance with the mandate stipulated in Law No. 12 of 1995 on Conservation, for prisoners who commit a crime of drug abuse, rehabilitation is mandatory. Once the prisoners are released, they will become clients of the organization and undergo guidance at the Bapas. Conclusion: The eradication of drug abuse has become a state effort to create generations of clean and drug-free nations. At the moment, the Indonesian government has established the problem of narcotics abuse as a very serious problem.